Analysis of The Ripeness And Weight of Fresh Fruit Bunches (FFB) on Oil Content And FFA - Husaini Firdaus; Rengga Arnalis Renjani; Nuraeni Dwi Dharmawati (Akademi Komunitas Perkebunan Yogyakarta, 2026)
The quality of palm oil is greatly influenced by the quality of the processed fresh fruit bunches (FFB), especially based on the maturity level and weight of the bunches. The difference in FFB characteristics can affect the oil yield and the level of FattyAcid (FFA) produced. This study aims to analyze the effect between the weight and maturity level of FFB on oil content and FFA content. The research method was carried out by sampling FFB in grading which was grouped based on weight (light 5 kg, medium 5–10 kg, and weight 10 kg) and fruit ripeness level (raw, ripe, and late ripe). The purpose of this study is to see the relationship between the weight of FFB on the oil content produced and FFA levels, analyze the influence of FFB maturity level on yield and FFA, analyze the proportion of FFB maturity level on FFA levels and yield in palm oil. The results of the study are expected to show the relationship between FFB weight and maturity level on oil yield and FFA levels. This research is expected to provide useful scientific information for palm oil mills in improving the efficiency of the FFB grading and processing process so as to produce palm oil with better quality.